2015
DOI: 10.1109/jlt.2014.2387891
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Effective Closed-Form GN Model Correction Formula Accounting for Signal Non-Gaussian Distribution

Abstract: Abstract-The GN model of non-linear fiber propagation has been shown to overestimate the variance of non-linearity due to the signal Gaussianity approximation, leading to maximum reach predictions for realistic optical systems which may be pessimistic by about 5% to 15%, depending on fiber type and system set-up. Analytical corrections have been proposed, which however substantially increase the model complexity. In this paper we provide a simple closed-form GN model correction formula, derived from the EGN mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 21 publications
(71 reference statements)
2
65
0
Order By: Relevance
“…This significantly simplifies the modeling of NLI in optical mesh networks as fiber spans are variably loaded. The approach is consistent with the observations in [22], [33].…”
Section: B the Xpm Assumptionsupporting
confidence: 90%
See 1 more Smart Citation
“…This significantly simplifies the modeling of NLI in optical mesh networks as fiber spans are variably loaded. The approach is consistent with the observations in [22], [33].…”
Section: B the Xpm Assumptionsupporting
confidence: 90%
“…Closed-form approximations, that predict the nonlinear interference power in coherent transmission systems, were derived for lossless fibers [3], [17] and lossy fibers using lumped amplification [13], [18]- [22] as well as for distributed Raman amplified links [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of of QPSK, only the channel of interest exhibits Gaussian modulation for validation purposes. For comparison the result of [21,Eq. (1)] is shown, which proposed a modulation format correction formula in the absence of ISRS.…”
Section: B Resultsmentioning
confidence: 99%
“…In the approach taken in this work, only the most dominant contribution, the cross-phase modulation contribution, is taken into account. It has been shown that this approach is sufficiently accurate with only a minor loss in accuracy [21], [24]- [27]. The approach is particularly accurate in high dispersive fibers such as standard single mode fiber (SMF) and systems with high symbol rates or channel spacings.…”
Section: Modulation Format Correctionmentioning
confidence: 99%
“…For the nonlinear fiber channel, a different distribution can achieve better performance in reach and throughput. In this work, we include the constellation excess kurtosis induced signal-to-noise ratio (SNR) gain; i.e., that the constellation shape can reduce the nonlinear interference, as analytically predicted by [5][6][7]. This method yields distributions that introduce less nonlinear interference than a MB distribution and more importantly outperform it in terms of mutual information, as demonstrated in [8].…”
Section: Introductionmentioning
confidence: 99%